Analysis of a Cantilever Beam - Rossow, Mark (McGraw-Hill's AccessEngineering., 2015)
Complicated polynomial equations describe the deflection and internal shear and moment distributions in a cantilever beam and are cumbersome to use in hand calculations. This Excel workbook employs these equations to automatically calculate maximum values, plots and tables of beam deflections, shear, and moments. The external reactions acting on the beam are also calculated. The user specifies beam length, load (concentrated forces, distributed forces, and concentrated moments) values and positions, and elastic modulus, and results appear in clearly labeled output cells, tables, and plots.